2019
DOI: 10.1177/0269215519864715
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of gradual attention training on language function in patients with post-stroke aphasia: a pilot study

Abstract: Objective: To investigate the effect of gradual attention training on language function with aphasia. Design: Randomized controlled trial. Participants: A total of 40 patients (mean age: 53.47 years) with post-stroke aphasia came from the stroke rehabilitation unit of rehabilitation department in the First Hospital of Jilin University, of which 13 (32.5%) had intracerebral hemorrhage, 28 inpatients and 12 outpatients, 11 women and 29 men, 34 within three-month stroke and 6 within three months to one year. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“… Liu et al (2019) used fingertip-based adaptive force control tasks to train attention function and found that the efficiency of the executive control network during ANT was significantly improved after training. Zhang et al (2019) found that gradual attention training seems to improve the language function of poststroke aphasia patients. Allcock et al (2009) studied the effects of computer-programed attention tasks in Parkinson’s patients and found that attention function training can improve patients’ walking ability and reduce the frequency of falls.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… Liu et al (2019) used fingertip-based adaptive force control tasks to train attention function and found that the efficiency of the executive control network during ANT was significantly improved after training. Zhang et al (2019) found that gradual attention training seems to improve the language function of poststroke aphasia patients. Allcock et al (2009) studied the effects of computer-programed attention tasks in Parkinson’s patients and found that attention function training can improve patients’ walking ability and reduce the frequency of falls.…”
Section: Discussionmentioning
confidence: 97%
“…Liu et al (2019) used fingertip-based adaptive force control tasks to train attention function and found that the efficiency of the executive control network during ANT was significantly improved after training. Zhang et al (2019) found that gradual attention training seems to improve the language function of poststroke aphasia patients. Allcock et al (2009)…”
Section: Discussionmentioning
confidence: 97%
“…Zhang et al 67 conducted a randomized controlled trial, in which the first group received impairment-specific language therapy, whereas the second group received additional gradual attention training. 68 Prior to and after treatment, language function was assessed by components of the WAB, including spontaneous speech, auditory comprehension, repetition, and naming, and WAB-AQ was calculated.…”
Section: Language Treatment Versus Language Plus Attention Trainingmentioning
confidence: 99%
“…Based on these findings, Murray and colleagues proposed that structured attention training may result in improvements limited to specific attention skills, whereas positive changes in untrained functions, including language, are less likely. Peach et al 63 Chronic PWA (n=4) L-SAT 64 Improvement on treatment tasks Western Aphasia Battery-Revised Aphasia Quotient (WAB-R AQ) 37 Object and Action Naming Battery 65 Discourse Comprehension Test 66 Language-specific attention training and domain-general attention training result in language improvement APT-III 62 Language treatment versus language plus attention training Zhang et al 67 Chronic PWA (n=40) Impairment-specific language therapy Impairment-specific language therapy + gradual attention training 68 Subtest scores and Aphasia Quotient WAB 24 Combination of language and attention training is more successful than language training alone Modarres et al 69 Case study with chronic PWA Language therapy targeting anomia Attentive rehabilitation of attention and memory 70…”
Section: Language Improvements Following Direct Attention Trainingmentioning
confidence: 99%
“…What is more? Attention treatments can effectively improve language function in PSA patients, there are some treatments that were proven effective, such as gradual attention training [6], Attention Process Training-3 [7], attention process training-II [8], et al…”
Section: Introductionmentioning
confidence: 99%